The forearm basilic vein looped transposition fistula as a tertiary option for upper limb vascular access. Issue 6 (November 2018) - Zielinski, Maciej; Inston, Nicholas; Krasinski, Zbigniew; Gabriel, Marcin; Oszkinis, Grzegorz
Introduction: The forearm basilic vein can serve as an option for haemodialysis access but may not be possible in cases where the wrist arteries are unsuitable. In this setting, the forearm basilic vein can be used in a looped transposition with a brachial artery anastomosis. Aims: The aims of this study were to assess the outcome of forearm basilic vein looped transposition as an option for vascular access. Material and methods: Data from January 2007 to December 2010 were prospectively collected and analysed. Outcome measures were operative success, complications, maturation and primary and secondary patency following 5 years of follow-up. Results: From a total of 583 patients receiving autologous vascular access for haemodialysis, 24 (4.1%) underwent a forearm basilic vein looped transposition. The median age was 60 years (range, 27–80 years), with a slight male predominance (13 male:11 female). Mean follow-up was 34 months (1–60 months). Two patients died and other three were transplanted with subsequent fistula closure. All procedures were successful (100%); however, maturation failure occurred in one case (4.2%). No serious perioperative complications were observed. In two cases, we observed late false aneurysm formation requiring intervention. Primary patency at 1, 2, 3 and 5 years was the following: 77%, 62%, 21% and 10%, whereas secondary patency was the following: 81%, 71%, 61% and 32%, respectively. Conclusion: Autologous forearm basilic vein looped transposition is an effective surgical procedure for the creation of access for haemodialysis. This may be a useful option in patients with compromised peripheral arterial diameter or flow and should be considered in patients with a suitable forearm basilic vein.